(untitled) (World Bulletin of Social Sciences, 2025)
This article explores the significance of integrating modern pedagogical technologies in creative education. It discusses the theoretical foundations of creativity in education, analyzes global and national literature on digital pedagogy, and highlights methods and strategies for applying innovative technologies such as ICT, STEAM, project-based learning, and gamification. The study identifies that creative education requires a flexible, learnercentered approach supported by interactive and digital tools. Results demonstrate that modern pedagogical technologies not only enhance creativity but also develop critical thinking, problem-solving, and collaboration skills essential for 21st-century learners.